Transit of NEAT1 and MTP11 to the plasma membrane and co-localization to vesicles support a role for exocytosis-mediated export in metal homeostasis - Vetal, Pallavi V.; Jaskolowski, Aime; Poirier, Yves (Physiologia Plantarum, 2025)
Understanding the role and mode of action of nutrient transporters requires information about their dynamic associations with plant membranes. Historically, apoplastic nutrient export has been associated with proteins localized at the plasma membrane (PM), while the role of endomembrane localization has been less explored. However, recent work on the PHOSPHATE 1 (PHO1) inorganic phosphate (Pi) exporter demonstrated that, although primarily localized at the Golgi and trans-Golgi network (TGN) vesicles, PHO1 does associate with the PM when clathrin-mediated endocytosis (CME) was inhibited, supporting a mechanism for Pi homeostasis involving exocytosis. We explored whether CME inhibition can identify other transporters that, although primarily localized at Golgi/TGN at steady-state level, also transit via the PM and are potentially involved in export via exocytosis. We found that, similar to PHO1, Golgi-localized transporters NA EFFLUX TRANSPORTER1 (NAET1) and METAL TOLERANCE PROTEIN11 (MTP11) relocate to the PM when CME is inhibited, both transiently in Nicotiana benthamiana and conditionally in Arabidopsis thaliana. Such PM re-localization of transporters upon CME inhibition is specific, since it does not occur with several other Golgi-associated transporters, including MTP5 and BIVALENT CATION TRANSPORTER 3 (BICAT3), as well as resident Golgi/TGN membrane proteins, such as alpha-1,2-MANNOSIDASE I (Man1) and VESICLE TRANSPORT V-SNARE 12 (VTI12). Additionally, we observed that NAET1, MTP11 and PHO1 all partially co-localize to vesicles. Overall, our study supports a role for synaptic-like vesicle-mediated exocytosis for both NEAT1 and MTP11 in nutrient transport in plants and highlights the importance of assessing the transient localization of Golgi/TGN proteins to the PM.